Advances in mesenchymal stromal cell therapy in the management of Crohn's disease. (1st February 2018) - Ibraheim, Hajir; Giacomini, Chiara; Kassam, Zain; Dazzi, Francesco; Powell, Nick
ABSTRACT: Introduction : The aim of therapy in Crohn's disease (CD) is induction and maintenance of remission, promotion of mucosal healing and restoration of quality of life. Even the best treatment regimes, including combinations of biologics and immunomodulators lack durable efficacy and have well documented side effects. Accordingly, there is an unmet need for novel therapies. Mesenchymal stromal cells (MSCs) are a subset of non-hematopoietic stem cells that home to sites of inflammation where they exert potent immunomodulatory effects and contribute to tissue repair. Their utility is being explored in several inflammatory and immune mediated disorders including CD, where they have demonstrated favourable safety, feasibility and efficacy profiles. Areas covered : This review highlights current knowledge on MSC therapy and critically evaluates their safety, efficacy and potential mechanisms of action in CD. Expert commentary : Building on positive early phase clinical trials and a recent phase 3 trial in perianal CD, there is considerable optimism for the possibility of MSCs changing the treatment landscape in complicated CD. Although important questions remain unanswered, including the safety and durability of MSC therapy, optimal adjunctive therapies and their sourcing and manufacturing, it is anticipated that MSCs are likely to enter mainstream treatment algorithms in the near future.